418 TRANSGENIC MICE WITH TRANSFORMING GROWTH FACTOR β TYPE II RECEPTOR DYSFUNCTION HAVE ATTENUATED HYPOXIA-INDUCED PULMONARY HYPERTENSION AND REMODELING. (1st January 2005) - Feng, J. A.; Li, P.; Xing, D.; Serra, R.; Oparil, S.; Chen, Y. F.
Abstract : We previously demonstrated that rats and mice exposed to chronic hypoxia exhibit increased pulmonary arterial pressure and right ventricular and pulmonary vascular remodeling with increased deposition of extracellular matrix (ECM) in lung. Transforming growth factor β (TGF-β) is known to increase proliferation of pulmonary arterial smooth muscle cells and production of ECM in pulmonary fibroblasts, suggesting a role for TGF-β in hypoxia-induced pulmonary hypertension and remodeling. This study tested the hypothesis that mice with dominant-negative TGF-β type II receptors (DNIIR) exhibit blunting of pulmonary hypertension and remodeling in response to hypoxia. Adult male wild-type (WT) and DNIIR mice were exposed to air or 10% O2 for 6 weeks. Mean right ventricular pressure (MRVP) was measured in anesthetized, spontaneously breathing mice as an index of pulmonary hypertension. RV free wall and the left ventricle and septum (LV + S) were weighed. Cross sections of lung were immunostained with α-smooth muscle actin (α-SMA) antibody for quantitaion of transformation of alveolar fibroblasts to myofibroblasts. Tissue weights were normalized by body weight using ANCOVA. Results (means ± SE, n = 7, ( p < .05, vs. air groups Δ p < .05, vs. WT groups) are shown in the Table . Exposure to hypoxia did not affect LV + S weight, but significantly increased MRVP, RV weight and number of α-SMA positive alveolar cells in WT mice. RV hypertension and hypertrophy and myofibroblast transformation were attenuated in DNIIR hypoxic mice compared to WT hypoxic mice. These data support our hypothesis that endogenous TGF-β plays an important role in regulating hypoxia-induced pulmonary hypertension and remodeling and cardiac hypertrophy via the TGF-β type II receptor.